Distinct immune-effector and metabolic profile of CD8+ T cells in patients with autoimmune polyarthritis induced by therapy with immune checkpoint inhibitors - Gente, Karolina; Kraus, Franziska V.; Carvalho, Rui A.; Lorenz, Holger; Hoerth, Christian; Günther, Janine; Klika, Karel D.; Graf, Jürgen; Diekmann, Leonore; Schank, Timo Emanuel; Christopoulos, Petros; Hassel, Jessica C.; et al. (Annals of the rheumatic diseases, 2022)
Objectives Rheumatic immune-related adverse events (irAE) such as (poly)arthritis in patients undergoing immune checkpoint inhibitor (ICI) treatment pose a major clinical challenge. ICI therapy improves CD8+ T cell (CD8) function, but CD8 contributes to chronic inflammation in autoimmune arthritis (AA). Thus, we investigated whether immune functional and metabolic changes in CD8 explain the development of musculoskeletal irAE in ICI-treated patients. - Methods Peripheral CD8 obtained from ICI-treated patients with and without arthritis irAEs and from AA patients with and without a history of malignancy were stimulated in media containing 13C-labelled glucose with and without tofacitinib or infliximab. Changes in metabolism, immune-mediator release, expression of effector cell-surface molecules and inhibition of tumour cell growth were quantified. - Results CD8 from patients with irAE showed significantly lower frequency and expression of cell-surface molecule characteristic for activation, effector-functions, homing, exhaustion and apoptosis and reduced release of cytotoxic and proinflammatory immune mediators compared with CD8 from ICI patients who did not develop irAE. This was accompanied by a higher glycolytic rate and ATP production. Gene-expression analysis of pre-ICI-treated CD8 revealed several differentially expressed transcripts in patients who later developed arthritis irAEs. In vitro tofacitinib or infliximab treatment did not significantly change the immune-metabolic profile nor the capacity to release cytolytic mediators that inhibit the growth of the human lung cancer cell line H838. - Conclusions Our study shows that CD8 from ICI-treated patients who develop a musculoskeletal irAE has a distinct immune-effector and metabolic profile from those that remain irAE free. This specific irAE profile overlaps with the one observed in CD8 from AA patients and may prove useful for novel therapeutic strategies to manage ICI-induced irAEs.
Gesehen am 12.06.2023